Erythromelalgia in Essential Thrombocythemia Is Characterized by Platelet Activation and Endothelial Cell Damage but not by Thrombin Generation - van Genderen, Perry J J; Lucas, Irene S; Strik, Roel van; Vuzevski, Vojislav D; Prins, Fransisco J; van Vliet, Huub H D M; Michiels, Jan J (Thrombosis and Haemostasis, 1996)
Erythromelalgia, a characteristic aspirin-responsive microvascular thrombotic complication in essential thrombocythemia (ET), may develop despite oral anticoagulant treatment or treatment with heparin, suggesting that the generation of thrombin is not a prerequisite for its development. To study this, a cross-sectional comparison of the plasma levels of thrombomodulin (TM), platelet factor 4 (PF4), β-thrombo-globulin (β-TG), prothrombin fragment 1+2 (F1+2) and total degradation products of fibrin(ogen) (TDP) was made between 5 ET patients suffering from erythromelalgia, 16 asymptomatic ET patients and 20 control subjects, and after treatment with aspirin, respectively. Furthermore, 2 ET patients with a history of erythromelalgia were studied at regular time intervals after discontinuation of aspirin until erythromelalgia recurred. As compared with asymptomatic ET patients and control subjects erythromelalgia was characterized by significantly higher β-TG and TM levels but no significant differences were detected in either F1+2 or TDP levels. Treatment of erythromelalgia with aspirin resulted in disappearance of erythromelalgic signs and symptoms, which was paralleled by a significant decrease of β-TG and TM levels. Histopathologic and immunohistochemical analysis of biopsies derived from erythromelalgic skin areas of 2ET patients showed that erythromelalgic thrombi stained positively for von Wille-brand factor opposed to only a weak fibrin staining. Our data suggest that erythromelalgia is caused by the intravascular activation and aggregation of platelets with subsequent sludging or occlusion of the acral arterial microvasculature. The generation of thrombin appears not to be essential for the formation of these platelet thrombi, thereby giving a plausible explanantion for the inefficacy of coumadin derivatives and heparin in the prevention and treatment of erythromelalgia in essential thrombocythemia.